Comparative analysis of banking crises in Argentina and Paraguay in the mid - 1990s - Ostalecka, Agnieszka (Uniwersytet Ekonomiczny we Wrocławiu, 2008)
Changes in financial systems, which occurred in the early 1990s, resulted in many profits, which improved their functioning. However, the scale and pace of changes, which took place in the financial systems environment, contribute to their greater vulnerability to shocks and financial crises. The aim of the article is a presentation of comparative analysis of two banking crises, which broke out in the mid-1990s in Latin America, i.e. in Argentina in 1994 and Paraguay in 1995. This analysis consists of 4 parts. Firstly, the article discusses the situation before the banking crises outbreak in two countries, referring to both the situation in the banking system and the whole economy as well. The second part of the article constitutes an identification of the main causes of the banking crises eruption. Following that, there is a presentation of the banking crises development and the authorities’ response to it including detailed measures, which were introduced to mitigate and resolve the crises in Argentina and Paraguay. The final part discusses the consequences to the banking system and the economy in both countries caused by the crises
Argumenta Oeconomica, 2008, No 1 (20), s. 83-106
Keywords: banking crises; source of crisis; crisis management; causes of crisis